Performativity and Event in 1960s Japan - Eckersall, P. author. aut Link
VIII, 183 p.
Keywords: Performativity and Event in 1960s Japan considers the artists and events in 1960s Japan. In response to the social upheavals of the 1960s, it shows how art interacted with society in unique and transformational ways, nterweaving arguments about the critical role of performance as an artistic medium and as a social dramaturgy.